Effect of general and local anesthesia on the vagal response characteristics during ganglionated plexus ablation. (24th May 2021) - Aksu, T; Yalin, K; John, L; Osorio, J; Winterfield, J; Aras, D; Gopinathannair, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: The effect of different anesthetics on the function of the autonomic nervous system (ANS) is not well known. As a relatively new treatment option, ganglionated plexus (GP) ablation aims to modify the behavior of the cardiac ANS to prevent some/all of the autonomic processes occurring in vasovagal syncope (VVS) by using endocardial ablation techniques. Purpose: The purpose of this study was to determine the effects midazolam and propofol on the vagal response (VR) characteristics during GP ablation in patients with vasovagal syncope (VVS). Methods: Forty consecutive patients undergoing GP ablation for VVS were divided to receive local anesthesia with midazolam (group 1, n = 29) or general anesthesia with propofol (group EA, n = 11). All GP sites were detected by using previously defined fragmented electrogram based strategy. VR was defined on 3 levels: 1) R-R interval increased by 50% (level 1); 2) R-R interval increased by 20-50% (level 2); and 3) R-R interval increase lower than 20% (level 3). Results: Baseline characteristics and mean follow-up times were comparable between groups. In both groups, the left superior GP (LSGP) was the most common GP site at which a VR was observed. However, there was a significant difference between groups for level of VR. While ablation on the LSGP caused a level 1 VR in 89.6% of cases in group 1, level 1 VR was seen in 22.2% of cases in group 2 (p < 0.0001). Similarly, ratio of level 1 VR during ablation on the left inferior GP (LIGP) was significantly lower in group 2 (44.8% vs 9%, p = 0.034). Once cut-off for VR was decreased to level 2, the ratio of (+) VR increased to 90.9% during ablation on the LSGP in group 2. Level 2 VR was detected in 45.4% of cases during ablation on the LIGP. Ratio of positive VRs in any level was lower than 20% during ablation on the right superior and inferior GPs in both groups. During a mean follow-up time of 12.1 ± 7 months, all but 2 (5%) of 40 patients were free of syncope. Conclusions: The autonomic nervous tone might be affected in different ways by local and general anesthesia. Propofol may reveal a shift in the sympathovagal balance toward sympathetic predominance which may cause a blunting on VR during GP ablation. Further randomized, controlled and multicenter studies should be performed to confirm these findings.